Pengaruh Kelainan Refraksi terhadap Terjadinya Vertigo pada Pasien di Poli Mata RSUD Dr. Moewardi - Fitri Prawitasari; . Suratno; Senyum Indrakila (Nexus Kedokteran Klinik, 2013)
Background: Refractive error occurs when the lights do not fall exactly at retina and cause blur vision. Visual system disorder causes balance disorder with vertigo symptom. This research aims to know the effect of refractive error on vertigo to patients at Ophthalmology Department of Dr. Moewardi Hospital. Methods: This research was observational-analitic with cross-sectional approach. The samples for this research were the patients at Ophthalmology Department of Dr. Moewardi Hospital aged 18-58 years old who has refractive error such as miopia, hipermetropia, or astigmatism while the second group (control) were people aged 18-58 years old without refractive error. Those samples were given questionnaire Vertigo Symptom Scale-Short Form and were tested for the balance to find out vertigo. Data was analyzed with Fisher Exact Test. Results: After the research to 25 patients with refractive error, 6 of 25 patients had vertigo. The second group, samples without refractive error had no vertigo. The result of Fisher Exact Test showed p value= 0,022 (p<0,05). Conclusions: There was effect of refractive error on vertigo to patients at Ophthalmology Department of Dr. Moewardi Hospital. Keywords: Refractive error, vertigo